Analysis of the Impact of Covid-19 on Pregnant Women on Preparation for Childbirth - Irnawati; Salmiani Abdul Manaf (Science Midwifery, 2022)
All routine services, including maternal and newborn health services, face many constraints during this pandemic. In the early stages of pregnancy, almost every pregnant woman begins to prepare for labor. There are many things that can be done to prepare, from preparing for the needs of the baby, the needs of the mother, psychological preparation, to preparing for the choice of a birthing facility. Welcoming babies into families is a habit, but during the Covid-19 pandemic, it's another story. Objective: The purpose of this Systematic Review is to analyze the effect of immunization services during the COVID-19 pandemic. Methods: Database search includes Google Scholar, Science Direct, and Pubmed with the keywords used are impact, anxiety; pregnant mother; maternity mother; childbirth, pandemic, COVID-19. The next stage is to select articles according to the criteria, which are published in 2017-2022 with the full text of 12 articles that meet the inclusion criteria. Results: Findings from 12 articles showed that the impact of COVID-19 on the preparation of pregnant women for childbirth in health facilities differed from maternal anxiety. In addition, the anxiety of pregnant women about childbirth greatly affects the mother's readiness to carry out prenatal care and preparation for delivery. And the effects of Covid-19 on childbirth have not been shown to be contagious to the newborn. However, mothers who are infected with Covid-19 must still follow health protocols, including self-isolation or separation from their newborn babies. Conclusion: the impact of covid 19 on preparation for childbirth is the anxiety of pregnant women, This anxiety can be reduced by providing guidance, counseling and education for pregnant women about transmission and routes of transmission. How to protect yourself from COVID-19 and its prevention. It is transmitted from pregnant women to babies. More importantly, if the mother is hesitant and afraid to go for a pregnancy check-up at the hospital for fear of contracting the virus from other people, a solution can be given to check her womb at the nearest midwife or clinic so that she can avoid contact with other people as well as when the delivery process arrives.